Modifying Properties of Aqueous Micellar Solutions by External Additives: Deep Eutectic Solvent versus Its Constituents. Issue 44 (29th November 2018) - Pal, Mahi; Behera, Kamalakanta; Yadav, Anita; Pandey, Siddharth
Abstract: Deep eutectic solvents (DESs) have emerged as nontoxic and inexpensive alternatives to both ionic liquids and common volatile organic solvents. Role of DESs in sustaining and effecting surfactant self‐assemblies has garnered interest only recently. Effect of addition of DESs Reline and Glyceline, constituted of salt choline chloride (ChCl) and different H‐bond donors (HBDs) urea and glycerol, respectively, in 1 : 2 mole ratios, on the physicochemical properties of four structurally‐different aqueous micellar solutions of anionic sodium dodecylsulfate (SDS), cationic dodecyltrimethylammonium bromide (DTAB), zwitterionic dodecyl sulfobetaine (SB‐12) and nonionic Triton X‐100 (TX‐100) is assessed. It is observed that the changes in the properties investigated are contingent, in most part, on the structure of the surfactant as well as on the identity of the DES. Properties of the anionic SDS micellar solutions are affected the most by the addition of the DESs. The change in the properties of an aqueous micellar solution due to the addition of a DES may not always be a result of the cumulative change due to the addition of the constituents of the DES. In general, the salt ChCl of the DESs is found to dominate the changes as compared to the HBDs urea/glycerol. Overall, DESs emerge as substances having potential to favorably modify the key properties of micellar media. Abstract : The effect of addition of deep eutectic solvents (DESs) on the physicochemical properties of the solutions containing micellar self‐assemblies at high concentration is presented. The extent of dissociation of DESs within aqueous micellar solution plays an important role in deciding the properties of these microheterogeneous media. The outcomes will increase the potential application of DESs in colloidal chemistry.